SLC38A2 provides proline and alanine to regulate postnatal bone mass accrual in mice - Shen, Leyao; Yu, Yilin; Karner, Courtney M. (Frontiers in Physiology, 2022)
Amino acids have recently emerged as important regulators of osteoblast differentiation and bone formation. Osteoblasts require a continuous supply of amino acids to sustain biomass production to fuel cell proliferation, osteoblast differentiation and bone matrix production. We recently identified proline as an essential amino acid for bone development by fulfilling unique synthetic demands that are associated with osteoblast differentiation. Osteoblasts rely on the amino acid transporter SLC38A2 to provide proline to fuel endochondral ossification. Despite this, very little is known about the function or substrates of SLC38A2 during bone homeostasis. Here we demonstrate that the neutral amino acid transporter SLC38A2 is expressed in osteoblast lineage cells and provides proline and alanine to osteoblast lineage cells. Genetic ablation of SLC38A2 using Prrx1Cre results in decreased bone mass in both male and female mice due to a reduction in osteoblast numbers and bone forming activity. Decreased osteoblast numbers are attributed to impaired proliferation and osteogenic differentiation of skeletal stem and progenitor cells. Collectively, these data highlight the necessity of SLC38A2-mediated proline and alanine uptake during postnatal bone formation and bone homeostasis.